Corruption in the Context of Moral Trade-offs. (January 2014) - Dungan, James; Waytz, Adam; Young, Liane
Moral psychology has begun to characterize the circumstances that lead people to commit moral violations. However, the decision to engage in corrupt behaviour may not always reflect a choice between right and wrong. Rather, the decision may represent a trade-off between competing moral concerns (for example, being fair and impartial to all versus loyal to one's own group). Taking the tension between fairness and loyalty as a case study, we demonstrate that the way people make trade-offs between competing moral norms predicts morally relevant behaviour, such as decisions to blow the whistle on unethical acts. We then suggest that this tension reflects a deeper distinction within our moral psychology, namely, a distinction between group-based norms (for example, loyalty) and norms that apply universally, independent of group membership (for example, fairness). Finally, we discuss what factors may influence the adoption of group-based versus group-independent norms and therefore, how these factors might deter or promote corruption. JEL: M14 Corporate Culture, Diversity, Social Responsibility